2022
DOI: 10.1111/jocn.16262
|View full text |Cite
|
Sign up to set email alerts
|

Learning in nursing home placement: A phenomenological study of student nurses’ lived experience

Abstract: Aim To explore first‐year student nurses’ lived experience of learning in clinical placement in nursing homes. Background Nursing homes traditionally represent students’ first clinical placement sites during nurse education, and nursing home residents’ care needs can provide opportunities for student nurses to acquire both fundamental and specialised nursing skills. In clinical placements, students have opportunities to apply and integrate theoretical knowledge, practical skills and ethical competence in a cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Interviews with student nurses, nurse educators and registered nurse mentors, as well as observations of mentorship practices (e.g., supervision and assessment), were conducted between June 2018 and March 2019 to gain insights, empathize and learn about the challenges faced by stakeholders during clinical placements. Findings from these studies have been reported elsewhere (see Aase et al, 2022; Dalsmo et al, 2022; Frøiland et al, 2021; Laugaland, Billett, et al, 2021; Laugaland, Kaldestad, et al, 2021). Inspired by Malterud (2012) first step (total impression) in systematic text condensation, we synthesized the findings from these studies from a “birds' eye” perspective before publishing them, as described in the overall study protocol (Laugaland et al, 2020).…”
Section: Results: the Co‐creative Processsupporting
confidence: 60%
See 1 more Smart Citation
“…Interviews with student nurses, nurse educators and registered nurse mentors, as well as observations of mentorship practices (e.g., supervision and assessment), were conducted between June 2018 and March 2019 to gain insights, empathize and learn about the challenges faced by stakeholders during clinical placements. Findings from these studies have been reported elsewhere (see Aase et al, 2022; Dalsmo et al, 2022; Frøiland et al, 2021; Laugaland, Billett, et al, 2021; Laugaland, Kaldestad, et al, 2021). Inspired by Malterud (2012) first step (total impression) in systematic text condensation, we synthesized the findings from these studies from a “birds' eye” perspective before publishing them, as described in the overall study protocol (Laugaland et al, 2020).…”
Section: Results: the Co‐creative Processsupporting
confidence: 60%
“…Interviews with pilot group participants Focus group interviews with registered nurse mentors (n = 30) and nurse educators (n = 9). ies have been reported elsewhere (see Aase et al, 2022;Dalsmo et al, 2022;Frøiland et al, 2021;Laugaland, Billett, et al, 2021;Laugaland, Kaldestad, et al, 2021). Inspired by Malterud (2012) first step (total impression) in systematic text condensation, we synthesized the findings from these studies from a "birds' eye" perspective before publishing them, as described in the overall study protocol (Laugaland et al, 2020).…”
Section: Workhopsmentioning
confidence: 99%
“…This pedagogical approach prioritises a student-centred learning model, enabling student nurses to construct their understanding actively rather than passively receiving the presented information [ 49 , 50 ]. This finding is important because nurse educators often fail to involve students in reflective-thinking activities during their educational process, resulting in a lack of student participation and difficulties in comprehending learning objectives [ 6 , 48 , 52 55 ]. Regarding this issue, Dalsmo et al [ 52 ] revealed that nurse educators were often ‘invisible’ in students’ learning processes during nursing home placement, hindering students’ ability to participate fully and comprehend the learning objectives.…”
Section: Discussionmentioning
confidence: 99%
“…Nurse educators positively experienced that pedagogical design features of the digiQUALinPRAX resource encouraged registered nurse mentors to provide a written assessment concerning both the strengths and weaknesses of student progression prior to summative assessment meetings, resulting in registered nurse mentors becoming more verbal during the meetings. Several studies have reported that nurse educators experience challenges in assessment meetings because of registered nurse mentors’ silence [ 42 , 52 , 56 ]. When nurse educators in our study experienced that registered nurse mentors wrote and verbalised what was expected from the students to work on during the remaining placement study, they were given opportunities to gear their student supervision towards the learning needs to focus on.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, there is a need for skilled and competent nurses in primary healthcare settings (Miura et al, 2020). Therefore, to educate competent nurses who can meet the needs of patients with complex health situations, a greater need for highly qualified nurse preceptors and high standard of preceptorship (Aglen et al, 2018), as well as for a learning environment that facilitates students' learning and their professional identity development (Dalsmo et al, 2022), are required.…”
Section: Introductionmentioning
confidence: 99%